The sets of α,β-statistically convergent and α,β-statistically bounded sequences of order γ defined by modulus functions - S. Ibrahim, Ibrahim; Listán-García, María C. (Rendiconti del Circolo matematico di Palermo, 2024)
In this research paper, our aim is to introduce the concepts of α , β -statistical convergence of order γ and α , β -statistical boundedness of order γ by using unbounded modulus functions in metric spaces. Furthermore, we obtain some relations between these concepts, and we provide some counterexamples to support our results.